Steroidogenic Factor-1 and Human Disease - El-Khairi, Ranna; Achermann, John C. (Seminars in Reproductive Medicine, 2012)
Steroidogenic factor-1 (SF-1) (Ad4BP, NR5A1) is a nuclear receptor that plays a key role in adrenal and reproductive development and function. Deletion of the gene encoding Sf-1 (Nr5a1) in mice results in severe developmental defects of the adrenal gland and gonad. Consequently, initial work on the potential effects of SF-1 disruption in humans focused on individuals with primary adrenal failure, a 46,XY karyotype, complete gonadal dysgenesis, and Müllerian structures. This is a rare phenotype, but has been reported on two occasions, because of alterations that affect key DNA-binding domains of SF-1. Attention then turned to a potential wider role of SF-1 in human adrenal and reproductive disorders. Although changes in SF-1 only very rarely cause isolated adrenal failure, it is emerging that variations in SF-1 are a surprisingly frequent cause of reproductive dysfunction in humans. In 46,XY disorders of sex development, a spectrum of phenotypes has been reported including severe and partial forms of gonadal (testicular) dysgenesis, hypospadias, anorchia with microphallus, and even male factor infertility. In 46,XX females, alterations in SF-1 are associated with primary ovarian insufficiency. Thus, SF-1 seems be a more significant factor in human reproductive health than was first envisioned, with implications for adults as well as children.
Keywords: steroidogenic factor-1 (SF-1); NR5A1; adrenal failure; 46,XY disorders of sex development (DSD); primary ovarian insufficiency (POI); infertility